2012
DOI: 10.1002/mop.26731
|View full text |Cite
|
Sign up to set email alerts
|

A compact asymmetric coplanar strip fed dual‐band antenna for DCS/WLAN applications

Abstract: A compact asymmetric coplanar strip (ACS) fed dual‐band antenna suitable for DCS/WLAN applications is presented. Dual‐band operation is achieved by modifying the signal strip of the ACS monopole. Parametric studies indicate that operating frequencies of the antenna are determined by the dimensions of the strip monopole. Measurements on the optimized antenna printed on an FR4 substrate with εr = 4.4 and height = 1.6 mm indicate good radiation characteristics with moderate gain. © 2012 Wiley Periodicals, Inc. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…In comparison to general coplanar waveguide (CPW)-fed antenna, an ACS-fed antenna structure will consume only 50% area by considering only half of the ground plane of CPW-fed structure. Table 2 shows the comparison of antenna size, operating bands and average peak gain of the proposed antenna with antennas reported in [19][20][21][22][23]. It is found that the proposed ACS-fed dual-band antenna is compact in size and it is covering all 2.4/5.2/5.8 GHz WLAN and 3.5/5.5 GHz WiMAX frequency bands with acceptable peak gain of 2.8 dBi.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In comparison to general coplanar waveguide (CPW)-fed antenna, an ACS-fed antenna structure will consume only 50% area by considering only half of the ground plane of CPW-fed structure. Table 2 shows the comparison of antenna size, operating bands and average peak gain of the proposed antenna with antennas reported in [19][20][21][22][23]. It is found that the proposed ACS-fed dual-band antenna is compact in size and it is covering all 2.4/5.2/5.8 GHz WLAN and 3.5/5.5 GHz WiMAX frequency bands with acceptable peak gain of 2.8 dBi.…”
Section: Introductionmentioning
confidence: 94%
“…To decrease the overall size of the antenna, some designs have been reported in [19][20][21][22][23][24][25][26][27] by using the concept of asymmetric coplanar strip (ACS)-fed. In comparison to general coplanar waveguide (CPW)-fed antenna, an ACS-fed antenna structure will consume only 50% area by considering only half of the ground plane of CPW-fed structure.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in order to minimize the overall size of an antenna, asymmetric coplanar strip (ACS) structure is introduced. The overall size of this antenna can be reduced to about one half of the common coplanar waveguide CPW-fed monopole antennas as reported in [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 96%
“…However, integration of these antennas with RF-MIC circuits with limited access to only service in WiMAX/WLAN frequency bands is a difficult task. Asymmetrical coplanar strip (ACS) feed multiband antennas provide easy integration solutions with RF-MIC have been reported in [11][12][13][14][15][16][17]. In general, an ACS feed antenna provides about 50% size reduction compared to the traditional CPW feed antenna as only one half the ground plane of the CPW structure is considered [16].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed antenna has the most compact dimensions and satisfactory stable gain and provides services in 2.4 GHz Bluetooth, 3.3/5.5 GHz WiMAX, 2.4/5.2/5.8 GHz WLAN frequency bands with acceptable gain of 4.5 dB. [12] 35 × 19 2.4/3.5/5.5 GHz Tri band [13] 37.5 × 24 2.4 GHz Dual band [14] 28 × 30 2.4/3.5/5.5 GHz Dual band [15] 21 × 19 2.4/5.2 GHz Dual band [16] 18 × 22 2.4/3.5/5.5 GHz Dual band [17] 17 × 17. Figure 1 shows the geometrical configuration of the proposed ACS feed triple-band antenna.…”
Section: Introductionmentioning
confidence: 99%